(untitled) (Heritage, 2024)
In this paper, we studied the incorporation of biblical and medieval genres into novels from the second half of the 20th century. The aim of our study was to indentify and isolate these genres, as well as to analyze them. It was important for us to examine how eriters adapted old, stable genres to postmodern poetics, and to determine how many elements are necessary to recognize a genre as such. We also, attempted to show the change in spiritual verticales in the novels we studied. The 20th century brings about the deconstruction of logocentric structures and the postmodern affirmation of the margins. The focus of interest now shifts to language in relation to writing, and dreams in relation to reality. The margin becomes a mirror of the conflict between the center and those who challinge it. The goal of deconstructing logocentric values and structures is not to reverse these values but to create new forms. The content of the indicated novels significantly influenced their very structure, as it stands in opposition to it. The novels „Nisci“, „Hazarski recnik“ and „Opsada crkve Svetog Spasa“ not only establish a critical relationship with the time they describe but also critically examine the structure of the novel itself. Distortion and deformation are consequences of the loss of order based on assured salvation, which the Christian world of the Middle Ages implied. Therfore, we attempted to answer the questions that arise before us: What makes a genre a genre? Furthermore, how many elements of a genre are „enough“ for us, as a readers/researchers, to recognize that genre? Additionaly, we are interested in the purpose and the extent to which biblical and medieval genres have been successfully utilized in the aforementioned novels.